1984
DOI: 10.1021/i200024a004
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic hydrodenitrogenation of quinoline in a trickle-bed reactor. Effect of hydrogen sulfide

Abstract: Studies at 350, 375, and 390 O C and 6.9 MPa showed that the presence of H,S (generated in situ from CS,) in the overall reaction network somewhat inhibits hydrogenation and dehydrogenation reactions but markedly accelerates hydrogenolysis reactions, for a net increase in the overall rate of hydrodenitrogenation (HDN). These effects are similar to those observed previously in vapor-phase reactions. H,S has little effect on the activation energies for the hydrogenation and dehydrogenation reactions, but it sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(63 citation statements)
references
References 3 publications
8
54
0
1
Order By: Relevance
“…It can be observed that the main reaction product was 1,2,3,4 tetrahydroquinoline (THQ1), and that decahydroquinoline (DHQ) was observed in minor amounts for all the catalysts. The conversion of quinoline by the ReS 2 (x)/supports catalyst can be depicted in the reaction scheme shown in Figure 5, in agreement with previously reported studies by several authors [4,5,6,9,10]. Figure 5 shows that the formation of DHQ compound can be produced through hydrogenation of quinoline (either via THQ1 or THQ5 intermediate compounds).…”
Section: Catalytic Testssupporting
confidence: 88%
See 1 more Smart Citation
“…It can be observed that the main reaction product was 1,2,3,4 tetrahydroquinoline (THQ1), and that decahydroquinoline (DHQ) was observed in minor amounts for all the catalysts. The conversion of quinoline by the ReS 2 (x)/supports catalyst can be depicted in the reaction scheme shown in Figure 5, in agreement with previously reported studies by several authors [4,5,6,9,10]. Figure 5 shows that the formation of DHQ compound can be produced through hydrogenation of quinoline (either via THQ1 or THQ5 intermediate compounds).…”
Section: Catalytic Testssupporting
confidence: 88%
“…Yang and Satterfield [5] studied the effect of hydrogen sulfide on the HDN of quinoline using NiMo/Al 2 O 3 catalyst. They found that the hydrogen sulfide inhibits hydrogenation and dehydrogenation reactions but markedly accelerates hydrogenolysis reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to HDS, the hydrogenation of the N-containing ring and in most cases also the hydrogenation of the benzene ring of quinoline are necessary steps in the two reaction pathways of Q-HDN via DHQ and OPA (cf. (11)(12)(13)(14)(15)(16)(17). The differences in the hydrogenation activities between various TMS will be more pronounced in the Q-HDN, which requires 8-14 H atoms to convert Q to hydrocarbons, than in the thiophene HDS which strictly needs only 4 H atoms, but may use up to 8 atoms.…”
Section: Autoclave Experimentsmentioning
confidence: 99%
“…Before discussing the selectivities of the various TMS catalysts it is useful to point out that the compounds present in the reaction product mixture can be divided into several categories with respect to their adsorption properties (14)(15)(16)(17). Because of their nonpolar character, the adsorption of the solvent and the hydrocarbon products of the Q-HDN can be neglected compared to the double-ring N-compounds.…”
Section: Autoclave Experimentsmentioning
confidence: 99%
See 1 more Smart Citation